Bone mineral density, pulmonary function, chronological age, and age at diagnosis in children and adolescents with cystic fibrosis - Márcio V.F. Donadio; Guilherme C. de Souza; Gabriele Tiecher; João P. Heinzmann-Filho; Taísa F. Paim; Patrícia X. Hommerding; Paulo J.C. Marostica (Brazilian Society of Pediatrics, 2013)
Objective: To assess bone mineral density in patients with cystic fibrosis (CF), and to correlate it with possible intervening variables. Methods: Children and adolescents diagnosed with CF, aged 6 to 18 years, followed at the outpatient clinic were included in the study. First, demographic data were collected and, subsequently, patients underwent a spirometric test. All patients answered the Cystic Fibrosis Quality of Life Questionnaire (CFQ) and underwent the six-minute walk test (6MWT) and bone densitometry (DXA). Results: A total of 25 CF patients were included, of which 56% were males. The mean age was 12.3 ± 3.4 years; mean height was 149.2 ± 14.4 cm; and mean weight was 44.4 ± 13.9 kg. Most results on pulmonary function and bone mineral density (BMD) were within normal limits. The mean forced expiratory volume in one second (FEV) was 92.5 ± 23.6 (% of predicted), mean forced vital capacity (FVC) was 104.4 ± 21.3 (% of predicted), and 1 mean BMD z-score was 0.1 ± 1.0. BMD was moderately correlated with FEV (r = 0.43, p = 0.03) and FVC (r = 0.57, p = 0.003). Regarding chronological age and age at diagnosis, a moderate and inverse correlation was also found (r = −0.55, p = 0.004; r = −0.57, p = 0.003, respectively). However, no significant correlations were found with the data from CFQ, 6MWT, and body mass index. Conclusion: Most patients had BMD within normal limits and presented a positive correlation with pulmonary function, as well as a negative correlation with chronological age and age at diagnosis.